Practical Interpretation of Liver Biopsy. - Liu, Xiuli; Lai, Jinping; Jhala, Nirag (Cambridge Scholars Publisher, 2020)
This volume brings together concise, essential, and up-to-date information on the most commonly encountered liver masses and lesions, as well as frequently seen neoplasms. It will be of use in a busy pathology practice setting for both general pathologists and pathology trainees. The checklists at the end of each chapter provide guidance on initiating the workup, generating the report, and suggesting subsequent studies. In addition, this book will be a good reference for liver pathology for hepatologists, other clinicians, and researchers who study the liver.